Utilization of Bio Slurry with Input of Buffalo Faeces and Water Hyacinth (Eichornia crassipes) With Various Doses of MOD (Microorganism Decomposer) on Productivity of Daun Kupu-kupu (Bauhinia Purpurea) - Buntora Situmorang; Tri Hesti Wahyuni; Nurzainah Ginting; Hasnudi .; Armyn Hakim Daulay (Jurnal Peternakan Integratif, 2017)
Abstract. This study aims to determine effects of utilization of Bio-Gas Slurry With buffalo Feces Input And water hyacinth with Various Dosage MOD (Microorganisme Decomposer) on Productivity of Bauhinia Purpurea. Research conducted at the field experimental, Samosir Sumatra Utara in April-November 2017. The design used in the study was split plot design with four replications. First factor (M): dosage decomposer, M1= 1 liters/150 kg and M2= 2 liters/150 kg. Second factor (P): dosage was fertilizier of Bio-Gas Slurry With buffalo Feces Input And water hyacinth(ton/ha/year), P0=0, P1=20, P2=40. The variable were studied fresh weight production, dry weight production, plant height and number of leaves. The results showed that dosage decomposer and dosage of fertilizer Bio-Gas Slurry significantly affect plant height, fresh weight production, dry weight production, and number of leaves Bauhinia Purpurea. The utilization of Bio-Gas With buffalo Feces Input And water hyacinth with Various Dosage MOD affect fresh weight production, dry weight production, plant height and number of leaves. It is concluded that dosage 2 liter/150 kg and application 40 ton/ha/year show higher on production of Bauhinia Purpurea..